The Effect Of Work Environment And Work Stress On Employee Performance CV. Mulya Steel, Tasikmalaya City - Rahmi Damayanti; Kusuma Agdhi Rahwana; Titin Patimah (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the effect of the work environment, work stress simultaneously and partially on the performance of employees at CV. Steel Mulya City of Tasikmalaya. The research method used was quantitative and the data were obtained directly from the results of distributing questionnaires to 40 respondents who were employees of CV. Steel Mulya City of Tasikmalaya. Data analysis techniques used statistical techniques such as validity and reliability tests for questionnaires and multiple regression analysis with F-test and t-test for proving the hypothesis. The results showed that simultaneously work environment and work stress have a significant effect on employee performance at CV. Steel Mulya City of Tasikmalaya. Furthermore, the work environment partially has a significant effect on employee performance at CV. Baja Mulya Tasikmalaya City, while work stress has a significant effect on employee performance at CV. Steel Mulya City of Tasikmalaya.